Fitting a distribution to survey data for the half-life of deviations from PPP - Mark Fisher (Federal Reserve Bank of Atlanta, 2015)
This note presents a nonparametric Bayesian approach to fitting a distribution to the survey data provided in Kilian and Zha (2002) regarding the prior for the half-life of deviations from purchasing power parity (PPP). A point mass at infinity is included. The unknown density is represented as an average of shape-restricted Bernstein polynomials, each of which has been skewed according to a preliminary parametric fit. A sparsity prior is adopted for regularization.
Keywords: C11; C14; F31; 330; nonparametric Bayesian estimation; Bernstein polynomials; simplex regression; importance sampling; PPP half-life deviations